One Extraordinary Lecturer One Article Indexed Minimum Sinta 3 Program to Improve Writing and Research Skills of Extraordinary Lecturers - Agustina, Ika; Nasrudin, Nasrudin; Sinaga, Rommel; Lubis, Reniwati; Putra, Syahripal (Journal Of Human And Education (JAHE), 2023)
This research aims to determine (1) the program "one extraordinary lecturer, one article with a minimum index of 3" in improving the writing and research skills of extraordinary lecturers; (2) the urgency of lecturers' scientific publications. In this research, a qualitative descriptive method was used. The data sources used in this research are previous research that is relevant to the research study. The data collection technique in this research is by reading sources that are relevant to the research study and then sorting the data that will be included. The final step in the research method is carrying out analysis using Miles and Huberman's perspective, including data presentation, data reduction and drawing conclusions. The results of this research show that; (1) aspects of extraordinary lecturers' writing skills that need to be improved are in the form of lecturer training and mentoring programs and training of trainer programs, while research aspects of extraordinary lecturers that need to be improved are scientific journal clinic programs and reference manager training; (2) In higher education, scientific articles published in reputable journals are an important component in increasing the value of university accreditation. For lecturers, the requirement for scientific publications from the Government can encourage lecturers to improve the quality and quantity of research and scientific publications.